Customary Laws and Land: Changes in Landholding System of the Karbis in Assam, India - Engtipi, Rashmi; Dhanaraju, Vulli (Indonesian Journal of Geography, 2024)
The purpose of this study is to look into the evolving trends in the landholding system of the Karbi tribe in Assam, India, as well as the nature of the customary laws that govern their land. This study challenged the Western notion of land ownership, which frequently promotes individual ownership and private ownership. The present study supported the idea of tribes’ customary rights over land management and communal property. Qualitative data were collected through field observations and oral interviews. This study employed content and discourse analysis methods to interpret the materials gathered. This research can be summarized by arguing that, with changing dynamics, the relationship is becoming clearer as survival dependency transitions from shifting cultivation to settled agriculture. Hill tribes have yet to gain legal entitlement to property in many regions, despite farming it for decades under communal ownership. The rise of private land rights is creating a situation in which more educated members of the society are abusing customary laws for personal gain. The landholding systems of the tribes in India, particularly the hill tribes of Assam, have been overlooked in studies for many decades. These overlooked research findings will contribute to the current knowledge and understanding of land management systems.